The Enigma of Imperial Protagonism in the Creation Tapestry: State of the Matter - Queiroz de Souza, Guilherme (Eikón / Imago, 2018)
The Creation Tapestry (11-12th centuries) can be considered the most famous and the most enigmatic work of the Catalan Romanesque. Our research focuses on the partially lost lower border, that shows the tops of a cross and of an imperial crown. The central enigma is – who carried these objects? If we consider their proportion/size, this character would have significant prominence in the embroidery. Some scholars have put forward hypotheses on the subject, pointing to three different possibilities: Empress Helena (ca. 250-330), Emperor Constantine I (272-337), or the basileus Heraclius I (ca. 575- 641), with more probability falling on one of the last two. We do not presume to discover the identity of this imperial character in the Tapestry, our main intention is to present the state of the matter; we also intend to comment some of the theories in the light of new evidence. An approximation to the identity of this character would lead us not only to a new interpretation of this famous work (its symbology, its function), but also to the mapping of the introduction of the imperial myth (either heraclian) in the Catalonia of the 11-12th centuries. That would help the understanding of the influence of this myth on religious belief, sociopolitical behavior, etc. constantinian or